Answer:
Step-by-step explanation:
3-(2x-5)=-4(x+2)
We simplify the equation to the form, which is simple to understand
3-(2x-5)=-4(x+2)
Remove unnecessary parentheses
3-2x+5=-4*(x+2)
Reorder the terms in parentheses
3-2x+5=+(-4x-8)
Remove unnecessary parentheses
+3-2x+5=-4x-8
We move all terms containing x to the left and all other terms to the right.
-2x+4x=-8-3-5
We simplify left and right side of the equation.
+2x=-16
We divide both sides of the equation by 2 to get x.
x=-8
Answer:
E(-1,3) F(3,-2) G(6,2)
Step-by-step explanation:
It's just simple addition and subtraction. The x-coordinate would add 2 since it is going to the right, which is positive. The y-coordinate would subtract 3 since going down be negative.
Answer:
Please see the attached file for the complete answer.
Step-by-step explanation:
This is the commutative property because you have 3*x*2*y and you turn the x and the 2 around. The commutative property states that a * b = b * a and therefore x*2 = 2*x.